2014
DOI: 10.1017/s1751731114000883
|View full text |Cite
|
Sign up to set email alerts
|

Imputation of ungenotyped parental genotypes in dairy and beef cattle from progeny genotypes

Abstract: The objective of this study was to quantify the accuracy of imputing the genotype of parents using information on the genotype of their progeny and a family-based and population-based imputation algorithm. Two separate data sets were used, one containing both dairy and beef animals (n = 3122) with high-density genotypes (735 151 single nucleotide polymorphisms (SNPs)) and the other containing just dairy animals (n = 5489) with medium-density genotypes (51 602 SNPs). Imputation accuracy of three different genot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 17 publications
2
8
0
Order By: Relevance
“…The mean within-animal genotype and allele concordance rates of 0.9993 and 0.9996, respectively between duplicate samples on the Illumina OvineSNP50 platform and also the near unity genotype and allele concordance rates of 0.9993 and 0.9997, respectively between the two Illumina platforms, are excellent and corroborate the respective values of 0.9989 and 0.9993 reported by Berry et al [3] using duplicate genotypes of 134 cattle that were genotyped on the Illumina BovineSNP50 beadchip. Using six samples from the human HapMap project, Hong et al [4] reported a mean genotype concordance rate of 0.9940 between duplicate samples on an Illumina platform and of 0.9987 between duplicate samples on an Affymetrix platform; all genotype comparisons undertaken by Hong et al [4] originated from the same genotyping laboratory.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The mean within-animal genotype and allele concordance rates of 0.9993 and 0.9996, respectively between duplicate samples on the Illumina OvineSNP50 platform and also the near unity genotype and allele concordance rates of 0.9993 and 0.9997, respectively between the two Illumina platforms, are excellent and corroborate the respective values of 0.9989 and 0.9993 reported by Berry et al [3] using duplicate genotypes of 134 cattle that were genotyped on the Illumina BovineSNP50 beadchip. Using six samples from the human HapMap project, Hong et al [4] reported a mean genotype concordance rate of 0.9940 between duplicate samples on an Illumina platform and of 0.9987 between duplicate samples on an Affymetrix platform; all genotype comparisons undertaken by Hong et al [4] originated from the same genotyping laboratory.…”
Section: Discussionsupporting
confidence: 88%
“…However, only two (experienced) laboratories were compared, which limited the possibility that a laboratory effect impacted genotype. Nonetheless, the high concordance rate between duplicate bovine samples reported by Berry et al [3], based on genotypes that were generated across multiple laboratories, provides further confidence that there is good genotype concordance across different service providers. Furthermore, most, if not all, of the discrepancies between duplicate genotypes on the platforms used in our study were actually due to a homozygous genotype of one replicate being called as a heterozygous in the other replicate, or vice versa.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Several studies have evaluated the accuracy of imputation from alternative-density genotype panels ranging from commercially available panels (Berry and Kearney, 2011;Berry et al, 2014) to custom-derived panels of SNP (Habier et al, 2009; Weigel et al, Figure 3. The mean allele concordance rate per animal across varying number of SNP selected using Feature Selection using Feature Similarity (diagonal lines), randomly (white bar), and uniformly (light gray bar), based on genomic characteristics (darkest bar), or by the block method (horizontal lined bar).…”
Section: Discussionmentioning
confidence: 99%
“…Beagle and FImpute are imputation software packages commonly used for cattle (Berry and Kearney, 2011;Berry et al, 2014;Carvalheiro et al, 2014). Beagle uses population LD to impute missing genotypes whereas FImpute exploits both family information and population LD.…”
Section: Imputation Algorithmmentioning
confidence: 99%